Comprendre le sens de l’action didactique des enseignants dans deux disciplines - Frédéric Maizières; Bernard Calmettes (Recherches en Éducation)
The research which is presented here aims to test a model to study the meaning that the teacher gives to his didactic action in different disciplines. The purpose is to refine the development of a model previously built as part of a grounded theory, that is to say a theory that takes into account both theoretical references that are not frozen and empirical research results that we present in the first part of this article. The data is built from observation and from the video of two sessions conducted in the same CM2 class in two disciplines, namely musical education and physic with the same teacher, and the implementation of two pragmatic interviews that were held before and after the sessions. The results allow us to define the relationship that the teacher has with all disciplines and more specifically with the two disciplines observed here. They also highlight the fact that if his didactic action primarily prevails over his "will ", time-related constraints may result in the end in his "not can" prevailing over his "will ".